Benefits of Caloric Restriction in Longevity and Chemical-Induced Tumorigenesis Are Transmitted Independent of NQO1. (4th May 2018) - Diaz-Ruiz, Alberto; Di Francesco, Andrea; Carboneau, Bethany A; Levan, Sophia R; Pearson, Kevin J; Price, Nathan L; Ward, Theresa M; Bernier, Michel; de Cabo, Rafael; Mercken, Evi M
Abstract: Caloric restriction (CR) is the most potent nonpharmacological intervention known to both protect against carcinogenesis and delay aging in laboratory animals. There is a growing number of anticarcinogens and CR mimetics that activate NAD(P)H:quinone oxidoreductase 1 (NQO1). We have previously shown that NQO1, an antioxidant enzyme that acts as an energy sensor through modulation of intracellular redox and metabolic state, is upregulated by CR. Here, we used NQO1-knockout (KO) mice to investigate the role of NQO1 in both the aging process and tumor susceptibility, specifically in the context of CR. We found that NQO1 is not essential for the beneficial effects of CR on glucose homeostasis, physical performance, metabolic flexibility, life-span extension, and (unlike our previously observation with Nrf2) chemical-induced tumorigenesis.